Dampak Hukum dan Psikologis Bagi Pelaku Pembunuhan Berencana - Putrawan, I Nyoman Alit (Ipso Jure, 2024)
Premeditated murder is a serious crime that has received great attention in the fields of law and criminal psychology. This research focuses on the legal and psychological impacts faced by perpetrators of premeditated murder, with the aim of gaining a deeper understanding of the consequences of these acts and finding more effective solutions in terms of punishment and rehabilitation. This research uses a qualitative approach with literature analysis and case studies. Data sources include academic literature, journal articles, and legal documentation. This analysis process will involve categorizing, interpreting, and synthesizing information from various sources to build a comprehensive understanding of the topic. This analysis will allow researchers to identify common themes, trends, and patterns in the literature, as well as reveal new insights or contradictions in current understanding of the legal and psychological impact of premeditated murder. The research results show that the legal consequences for perpetrators of premeditated murder are often very severe, including the death penalty or life imprisonment. But the research also revealed that many perpetrators experienced serious psychological problems, including post-traumatic stress disorder and antisocial personality disorder. Factors such as socioeconomic background, history of trauma, and exposure to violence contribute to the commission of these crimes. This research emphasizes that the legal approach to premeditated murder must consider the psychological impact and social background of the perpetrator. The importance of an interdisciplinary approach in dealing with cases stands out, and the results of this research can provide insights for the development of more effective legal policies and rehabilitation programs.